Performance Comparison between Salient and Segmental Rotors Single-Phase FEFSM Using Non-Overlap Windings for Home Appliances - Omar, M. F.; Sulaiman, E.; Soomro, H. A.; Jusoh, L. I. (International Journal of Engineering and Technology, 2018)
Field excitation flux switching machines (FEFSMs) in which their torque performance produced by interaction between armature and field excitation (FE) coils have been widely designed for various applications. In this regard, three-phase salient rotor FEFSM with overlap windings is considered the most suitable candidate for high speed applications because of their advantages of flux controllability, and robust due to single piece of rotor structure. However, the overlap windings cause a high copper loss, hence efficiency of the motor becomes low and higher stack length. Besides, the salient rotor structure is found to produce low torque performance due to the longer flux path in stator and rotor yielding weak flux linkage. In this paper, a new single-phase FEFSM using non-overlap windings between armature coils and FE coils is proposed. Both non-overlap windings FEFSMs with salient and segmental rotors have been designed using JMAG Designer version 15 and the investigation process is conducted via 2D finite element analysis. The proposed motor performances verification has been done by comparing the results of flux linkage, flux line and distribution, flux strengthening, various torque capability, and torque-power versus speed characteristics. As a conclusion, single-phase non-overlap windings FEFSM using segmental rotor with power, torque and speed capabilities of 277.5 W, 0.91 Nm and 2,899 rpm, respectively considered as the best candidate for low torque high speed applications.